Principals' Strategies in Developing a Child-Friendly School Culture through a School Based Management Approach - Jufri (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
This study examines the principal’s strategy in developing a child-friendly school culture through a School Based Management approach at SDN 3 Katobengke. The study is grounded in the view that child-friendly school culture should not be understood merely as a formal program, but as an integral part of school governance that promotes a humane, participatory, and student-centered educational environment. In this context, School-Based Management provides schools with the autonomy and flexibility to formulate policies, strengthen stakeholder participation, and develop institutional practices that are responsive to students’ needs. This research employed a qualitative approach with a case study design. The study was conducted at SDN 3 Katobengke, Baubau City. Data were collected through in depth interviews, observation, and documentation involving the principal, teachers, school staff, the school committee, parents, and students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. Data trustworthiness was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that the principal’s strategy in developing a child-friendly school culture was carried out through the strengthening of school policies, participatory leadership, stakeholder involvement, the creation of a supportive learning environment, and the habituation of positive values in daily school life. The principal acted not only as an administrator but also as a strategic leader who mobilized teachers, involved parents, and directed school governance toward students’ best interests. The study concludes that School Based Management can function effectively in strengthening child-friendly school culture when supported by visionary leadership, collaborative governance, and consistent implementation of child-friendly values in everyday school practices.